2016
DOI: 10.1515/bjdm-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ergonomic risks during dental work

Abstract: SummaryAim: The purpose was to assess ergonomic risk level in dentistry, which may contribute to manifestation of musculoskeletal disorders (MSD). Methods and Materials: The study included ten dentists, postgraduate students, mean age (33 ± 3.4). Participants were asked to perform typical dental examination in standing and sitting positions. The surface electromyography (EMG) was recorded during dental work from both left and right shoulder muscles: descendent trapezius muscle (T); back muscles: erector spinae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 14 publications
0
41
0
2
Order By: Relevance
“…In the studies found, it was observed that the dorsal trunk region was the most evaluated, with the trapezius muscle, both in its ascending and descending portion, being the most studied muscle [10,11,12,15,18,19,24,27,28,30,35]. Akesson et al, [18] used surface EMG for evaluation of the demands experienced by dental hygienist during their working routine, recording the descending part of the upper trapezius muscle bilaterally.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the studies found, it was observed that the dorsal trunk region was the most evaluated, with the trapezius muscle, both in its ascending and descending portion, being the most studied muscle [10,11,12,15,18,19,24,27,28,30,35]. Akesson et al, [18] used surface EMG for evaluation of the demands experienced by dental hygienist during their working routine, recording the descending part of the upper trapezius muscle bilaterally.…”
Section: Resultsmentioning
confidence: 99%
“…The erector spinae was also studied by Pejčić et al, [27] that evaluated the back inclination and muscle activities of the m. erector spinae, m. trapezius descendens, m. sternocleidomastoideus and m. splenius capitis of dentists during a typical dental examination of patients in standing and sitting positions. Likewise, the m. erector spinae, m. trapezius descendens, m. sternocleidomastoideus and m. splenius capitis during sitting and standing position was evaluated in another study to assess ergonomic risk level in dentistry by performing typical dental examination on the patients in standing and sitting positions [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many factors in dental profession, such as specific working environment, fine, controlled dental work, full commitment to the patient, cause that dentists often neglect themselves and do not pay attention to adequate working posture. Dentists often work in inappropriate working position, which is one of the main risk factors for development of MSD 9‐11 …”
Section: Introductionmentioning
confidence: 99%